Efek Kurkumin Pada Kunyit (Curcuma longa) Sebagai Pengobatan Kanker Lambung - Firantika Dias Puteri (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background :Cancer or malignancy is a group of diseases characterized by uncontrolled growth and spread of normal cells. One of the cancers that is still a problem in the world is gastric cancer. Gastric cancer is one of the main contributors to high mortality in the world, especially among men in old age. There are several treatment methods that are commonly used, such as surgery, radiation and chemotherapy. The choice of the method depends on the type and stage of tumor development. Chemotherapy is one of the treatment methods of choice, but the success rate of this treatment is limited due to chemoresistence. Herbal plants are one of the active compounds that are believed to be an alternative as anticancer because they have minimal side effects. One of the plants that can be used is turmeric (Curcuma longaI). Purpose: find out more about the benefits of turmeric as a stomach cancer treatment. Method: The method used by the author is literature study from various national and international journals. This method is used with the aim of increasing knowledge and understanding of the topics discussed by presenting published material by summarizing the material that has been published and providing factual information or new analysis from relevant literature reviews and then comparing the results in the article. Results: Curcumin compounds from the Curcuma longa plant can play a role in inhibiting cancer cell proliferation, anti-inflammatory, carcinogenic inhibition, immunomodulatory, antiestrogem and antiangiogenesis. Its role in tumorigenesis is also mediated through expression of genes that suppress apoptosis, mediate proliferation, invasion and angiogenesis. Conclusion: The curcumin content in turmeric can act as an anticancer, such as stomach cancer.